Cohesive Devices In EFL Students’ Expository Writing - Hanif Nurcholish Adiantika (University of Kuningan, 2015)
This study aims to investigate the use of cohesive devices in students’ expository writing. In particular, the study focuses on types of cohesive device used by the students and how cohesive devices contribute to their writing. This study employs qualitative research through a case study design. Public senior high school in Kuningan is chosen as the site for this study. Nine students of twelfth grade are involved in the study as the respondents. Documents of nine students’ expository writings are the data of this study. The data are analyzed by using the concept of cohesive devices proposed by Halliday and Hasan (1976) which covers reference, substitution, ellipsis, conjunction, and lexical cohesion. Analyses show that the respondents only use four cohesive devices in their writing i.e. reference, substitution, conjunction, and lexical cohesion. These devices also contribute to the process of keeping track of the participants, avoiding repetition and text redundancy, enhancing logical connection between parts of text, and engaging the readers to the core argument of the text. The study infers that it is still problematic although most of the students apply many cohesive devices in their writing. This is because students have not received sufficient training concerning how to use appropriate cohesive devices. Therefore, they should be guided to utilize appropriate cohesive devices in their writing.Keywords: cohesive devices, cohesion, EFL students, expository writing, case study